High prevalence of willingness to use direct‐acting antiviral‐based regimens for hepatitis C virus (HCV) infection among HIV/HCV coinfected people who use drugs. Issue 9 (13th March 2017) - Socías, ME; Ti, L; Dong, H; Shoveller, J; Kerr, T; Montaner, J; Milloy, M‐J
Abstract : Objectives: Despite the high burden of hepatitis C virus (HCV)‐related morbidity and mortality among HIV‐positive people who use illicit drugs (PWUD), uptake of interferon‐based treatments for HCV infection has been negligible among this group. Direct‐acting antiviral (DAA) therapies offer an opportunity to expand treatment access among this population. The aim of this study was to explore willingness to use DAA‐based regimens among HIV/HCV‐coinfected PWUD in Vancouver, Canada. Methods: Data were drawn from the AIDS Care Cohort to evaluate Exposure to Survival Services (ACCESS), a prospective cohort of HIV‐positive PWUD. Using logistic regression analyses, we investigated factors associated with willingness to use DAA‐based regimens among HIV/HCV‐coinfected participants. Results: Of 418 HIV/HCV‐coinfected PWUD surveyed between June 2014 and May 2015, 295 (71%) were willing to use DAA‐based regimens. In multivariable analysis, participants enrolled in methadone maintenance therapy [adjusted odds ratio (AOR) 1.61; 95% confidence interval (CI) 1.04–2.51], those with a recent assessment by an HCV specialist (AOR 2.02; 95% CI 1.28–3.19) and those who perceived that HCV infection was affecting their health (AOR 2.49; 95% CI 1.41–4.37) were more likely to be willing to use DAA‐based regimens. Conclusions: Overall, this study found a high prevalence of willingness to use DAA‐based regimens among HIV/HCV‐coinfected PWUD in Vancouver. Importantly, enrolment in methadone maintenance therapy was positively associated with willingness, suggesting that integrated models of HIV, HCV and addiction care should be explored as a way to address HCV‐related morbidity and mortality among HIV/HCV‐coinfected PWUD.